Reconstructing Arabic Communicative Competence through a Communicative Approach: A Case Study of Listening and Speaking Instruction among Non-Native Learners in Southern Thailand - Haris Chehna; Suparman Syukur; Suja'i Suja'i (Yayasan Darussalam Bengkulu, 2025)
This study aims to analyze the reconstruction of Arabic communicative competence through the application of communicative approaches in learning listening and speaking skills in native non-speaking learners in Southern Thailand. This study uses a qualitative approach with a multi-case study design carried out in several Islamic educational institutions, with Assiroh Islamic School as the main case. Data was collected through in-depth interviews, participatory observations, and document analysis, then analyzed using thematic analysis iteratively to produce interpretations based on participants' experiences and institutional context. The results of the study show three main findings. First, the reconstruction of Arabic communicative competence takes place through the integration of four dimensions of communicative competence, namely linguistic, sociolinguistic, discourseal, and strategic competence, thereby shifting the orientation of Arabic language learning from mastering linguistic structures to using language meaningfully in the context of authentic communication. Second, learning interactions based on a communicative approach transform students' learning experiences by changing the role of teachers as facilitators and students as active language users through dialogue, role-playing, collaborative discussions, presentations, and the use of authentic learning resources that encourage negotiation of meaning, active participation, and increased confidence in communication. Third, the successful implementation of the communicative approach is supported by the pedagogical competence of teachers, the functional relevance of Arabic in the Islamic education environment, and the use of authentic learning media, while the limited opportunities to use Arabic outside the classroom, the heterogeneity of students' initial abilities, and the still dominant learning culture oriented to grammar and memorization are the main obstacles in the development of communicative competence. These findings confirm that the development of Arabic communicative competence is not only determined by the application of communicative learning techniques, but also by the dynamic interaction between pedagogical practices, institutional ecology, and the sociocultural context of learners. This research makes a conceptual contribution by offering a context-sensitive framework for the reconstruction of Arabic communicative competence, thereby expanding the theory of Communicative Language Teaching in a multilingual Islamic education environment and providing an alternative perspective for the development of Arabic language learning that goes beyond traditional structural paradigms.